Empati för offer av psykiskt våld: en komparativ studie rörande perspektivtagande - Fors,Love; Nipstad,Hugo (2023)
This quantitative study was aimed to examine respondents' empathy towards victims of psychological abuse. Furthermore the study’s ambition was to reveal differences in empathy on three levels; gender, perspective and type of violence. Earlier research indicates that women show greater empathic ability than men. Moreover psychological abuse is perceived as more severe when seen from a third person perspective rather than a first person perspective. The study conducted a quantitative survey consisting of 43 participants, all of whom were recruited through social networks using convenience sampling. The survey consisted of 46 questions and was divided into two distinct parts. First part consisted of the ECPT scale, while the second part consisted of fictional scenarios of psychological abuse. The study conducted a Mixed ANOVA comparing all three independent variables on empathic ability. Results showed that in contrast to earlier research, narratives in a first person perspective invoked higher levels of empathy than narratives in a third person perspective. However the result was consistent with earlier research in regards to gender, where women showed greater empathic ability than men. There were no significant results in regards to type of violence on empathic ability. Conclusively the study sees gender and societal norms as a contributing factor to women wanting to be more empathic and therefore score higher than men. Regarding perspective and narrative, the study explains the contradicting result by highlighting the importance of language and narrator.
Keywords: Perspective-taking; empathy; narratives; moral principles; psychological abuse; Perspektivtagande; empati; moraliska principer; narrativ & psykiskt våld